The poverty of the comparative orthodoxy: cultural criminology, perspectival realism and conceptual variation - Frauley, Jon (International journal of law, crime and justice, 2021)
Comparative criminology has long struggled with the concept and object of culture while advances in culturally oriented criminologies have been ignored. Likewise, culturalists have ignored attempts at comparison for transcending milieu and are mired by theoretical and methodological eclecticism. Comparative criminology will benefit from engaging with conceptualisations of culture found in culturalist works and culturally oriented criminologies will benefit from an expanded focus beyond localised contexts to reveal and grapple with greater varieties of (sub)cultural variation. After bringing a qualified cultural criminology to comparative criminology I draw on the philosophy of science known as perspectival realism to address some epistemological and methodological problems in each camp. I argue an interpretive comparative criminology focused in identifying and generating conceptual variation is better suited to understand and grapple with the political-cultural dramatisations that are indicated by the statistical data of interest to those wedded to the comparative, nomothetic orthodoxy.